PENEGAKAN HUKUM PIDANA PEMILU/PILKADA ELEKTRONIK PADA PEMILU/PILKADA SERENTAK 2024 - Pirmansyah, Redi; Junaidi, Junaidi; Merta, Martindo (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2023)
ABSTRACTElection criminal provisions regulated in Law Number 7 of 2017 concerning General Elections only cover 80 articles of election crimes and do not comprehensively regulate election criminal acts in the electronic field for all applications to be used in the 2024 Election. This can create a legal vacuum or the obscurity of election crimes in the field of electronics in the use of electronic election systems. Although Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions generally regulates electronic crimes, the 11 articles of electronic crimes do not regulate electronic crimes at the time of the election stage. The electronic election crime above will guarantee protection for all applications that will be implemented by the KPU in carrying out the 2024 election stages. In the context of this crime, the